2022
DOI: 10.1002/berj.3795
|View full text |Cite
|
Sign up to set email alerts
|

A critical consideration of ‘mental health and wellbeing’ in education: Thinking about school aims in terms of wellbeing

Abstract: This paper examines ideas about mental health, wellbeing and school education to illustrate important issues in the relationship between mental health and education. The Covid crisis has amplified the pre‐existing mental health problems of children and young people in England and recognition of the opportunities in schools to address these. The paper gives an overview of child and adolescent mental health services and how they position the role of schools. It examines prominent concepts of mental health and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…The current challenges taking place in various parts of the globe, such as the COVID-19 pandemic, displacement and forced migration due to war and conflict, and climate change, have exacerbated the mental health issues faced by children and young people. The pandemic has led to an increase in mental health difficulties, particularly amongst those already at risk ( OECD, 2020a ; United Nations Educational, Scientific and Cultural Organisation [UNESCO], 2020 ) and underlined the opportunities for schools to address these issues ( Norwich et al, 2022 ). Between ten to twenty percent of school children experience mental health issues during their school years, with half of the mental health problems developing before the age of fourteen ( WHO Regional Office for Europe, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The current challenges taking place in various parts of the globe, such as the COVID-19 pandemic, displacement and forced migration due to war and conflict, and climate change, have exacerbated the mental health issues faced by children and young people. The pandemic has led to an increase in mental health difficulties, particularly amongst those already at risk ( OECD, 2020a ; United Nations Educational, Scientific and Cultural Organisation [UNESCO], 2020 ) and underlined the opportunities for schools to address these issues ( Norwich et al, 2022 ). Between ten to twenty percent of school children experience mental health issues during their school years, with half of the mental health problems developing before the age of fourteen ( WHO Regional Office for Europe, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Like ours, such research emphasises the relational nature of teachers' and students' experiences of wellbeing at school (Billington et al, 2022;Culshaw & Kurian, 2021;Graham et al, 2016). Noddings (2010Noddings ( , 2012Noddings ( , 2013 outlines how pedagogies of care in teaching can cultivate wellbeing, as the healthy growth of whole persons (Hordern, 2021). In addition to Noddings, Culshaw and Kurian (2021) emphasise the present orientation and critical professional judgement required of teachers in order to cater for the real needs of students as opposed to their 'presumed needs', termed 'virtue caring'.…”
Section: Locating Wellbeing In Te Aching Pr Acticementioning
confidence: 83%
“…One potential solution is to incorporate mental health support into the school curriculum. For example, a study found that the inclusion of mindfulness-based stress reduction techniques in a post-COVID-19 school curriculum can help reduce student stress levels and improve mental health outcomes [ 36 , 37 ]. This approach has the potential to help students develop the skills they need to manage stress and anxiety and may be an effective way to promote overall well-being among students.…”
Section: Resultsmentioning
confidence: 99%